Complex transcriptional control of the AZFa gene DDX3Y in human testis - Rauschendorf, Marc-Alexander; Zimmer, Jutta; Hanstein, Regina; Dickemann, C; Vogt, Peter H. (International journal of andrology, 2011)
The human DEAD-box Y (DBY) RNA helicase (aka DDX3Y) gene is thought to be the major azoospermia factor a (AZFa) gene in proximal Yq11. Men with its deletion display no somatic pathologies, but suffer from complete absence of germ cells. Accordingly, DDX3Y protein is expressed only in the germline in spermatogonia, although the transcripts were found in many tissues. Here, we show the complex transcriptional control of a testis-specific DDX3Y transcript class with initiation at different sites upstream of the gene's open reading frame (5'Untranslated Region; UTR) and with polyadenylation in their proximal 3'UTR. The most distal transcriptional start site (TSS; ∼1 kb upstream) was mapped in MSY2, a Y-specific minisatellite. As this testis-specific 5'UTR was subsequently processed by three alternative splicing events, it has been tentatively designated 'exon-T'(estis). The MSY2 sequence unit was also found upstream of the mouse Ddx3y gene. However, only after its tandem amplification on the Y chromosome of Platyrrhini (new world monkeys) and Catarrhini (old world monkeys) did MSY2 become part of a novel distal promoter for DDX3Y expression in testis tissue and provides a second transcriptional start site (T-TSS-II) in Catarrhini. We therefore suggest that the development of a novel distal DDX3Y promoter in primates, which is activated only in testis tissue, is probably part of the gene's germline translation control.